PERLINDUNGAN HUKUM BAGI PEMBELI ATAS WANPRESTASI PENGEMBANG PERUMAHAN DALAM JUAL BELI RUMAH (STUDI PUTUSAN MAHKAMAH AGUNG NO. 2052/K/PDT.2017) - DANIEL FIRMAN SILAEN (Journal Law of Deli Sumatera, 2021)
The agreement made by the housing developer as stated in the Sale and Purchase Binding Agreement (SPBA) is first made before entering into other agreements in the house buying and selling process. In the implementation of SPBA between housing developers and consumers, there may be default acts committed by one party, resulting in losses incurred to the other party. Defaults in the implementation of housing SPBA in installments between housing developers and consumers can also occur. The type of research used in this study is normative juridical research. The nature of this research is descriptive analytical. The data used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The result of the discussion in this study is that the obligation of the buyer has been fulfilled in its entirety by paying the price of land and house buildings in full amounting to Rp 210,000,000 (two hundred and ten million rupiah). The relationship between the legal responsibilities of the housing developer PT Indojaya Pan Pratama in the case of refusal to make AJB is due to the stages of payment for land and house buildings that have not been accepted by the company as a seller. Legal protection for buyers/consumers for default is in accordance with the provisions of Articles 1365 and 1367 of the Civil Code regarding claims for compensation for default/unlawful actions from the seller who refuses to make AJB for the legal rights and interests of the buyer/consumer due to embezzlement committed by marketing employees of the selling company which is the responsibility of the selling company.